IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI PADA MATA KULIAH EKONOMI PENDIDIKAN - I Dewa Gede Aditya Satria Wibawa (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to improve student learning outcomes in the Economics Education Study Program in the Economics of Education course through the application of the Problem-Based Learning (PBL) model. This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 10 second-semester students in the Economics Education Study Program at PGRI Mahadewa Indonesia University in the even semester of the 2025/2026 academic year. Data collection techniques used observation and learning outcome tests. Data were analyzed descriptively and quantitatively by calculating the average score and classical learning completion. The results showed an increase in student learning outcomes, with the average score in the first cycle being 68.5 with a classical completion of 60%, while in the second cycle it increased to 82.3 with a classical completion of 90%. Thus, the application of the Problem-Based Learning (PBL) model has been proven to improve student learning outcomes through a planned learning cycle.